SOLID-SOLUTION AQUEOUS-SOLUTION REACTIONS BETWEEN JAROSITE (KFE3(SO4)2(OH)6) AND ITS CHROMATE ANALOG - Baron D.; Palmer C.D. (My University, 2002)
The sulfate mineral jarosite (KFe3(SO4)2(OH)6), its chromate analog (KFe3(CrO4)2(OH)6), and seven precipitates with intermediate compositions (KFe3(CrXS(1-X)O4)2(OH)6) were synthesized. The unit cell volume of the precipitates is closely represented by a linear function of composition, suggesting a continuous solid solution. This solid solution dissolves stoichiometrically according to KFe3(CrXS(1-X)O4)2(OH)6 + 6H+->K++3Fe3++ 2X CrO42- + (2 - 2X) SO42- + 6H2O and reaches stoichiometric saturation after approximately 40 d. Log KSS values calculated from samples taken after 1090 d are consistently lower than what would be expected for an ideal solid solution, indicating that the excess free energy of mixing, GE, is negative. GE calculated from the log KSS values can be closely modeled by the one-parameter Guggenheim expansion GE = XCrJar XJar RT a0 where a0 is -4.9 +/- 0.8, XCrJar and XJar are the mole fractions of KFe3(CrO4)2(OH)6 and KFe3(SO4)2(OH)6 in the solids, R is the gas constant, and T the absolute temperature. Based on the calculated excess free energy, a Lippmann diagram with a modified abscissa was constructed.